Successfully Mentoring Undergraduates in Research: A How To Guide for Mathematicians. Issue 3 (16th March 2017) - Dorff, Michael; Henrich, Allison; Pudwell, Lara
Abstract: Undergraduate research occurs in a variety of mathematical fields and in diverse settings, but all mentors of undergraduates face a number of common considerations. This article is a brief guide to help faculty with various levels of previous mentoring experience lead students in research projects. In particular, we discuss the issues of picking appropriate research problems, recruiting students, setting expectations, moving research forward, and helping students to communicate their work.